2009
DOI: 10.1021/bi900219c
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Membrane Disruption by Amyloid Fibrils Involved Intermolecular Disulfide Cross-Linking

Abstract: Accumulating evidence has strongly suggested that amyloid fibrils of protein or peptide are cytotoxic. Fibrillar species appear to lead to disruption of cell membrane structures and thereby cause cell death. In this study, human erythrocytes were used as an in vitro model to examine the disruptive effect of lysozyme fibrils on the plasma membrane. Both the protofibrils and mature fibrils induced hemolysis and aggregation of erythrocytes. Treating ghost membranes with the fibrils resulted in aggregation of memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…ThT fluorescence was measured in a mixture of 33 g/mL lysozyme and 10 M ThT with excitation at 440 nm and emission at 484 nm in a Perkin Elmer LS55 spectrofluorimeter. The emission spectra of ANS fluorescence in the presence of lysozyme fibrils were recorded between 400 and 600 nm using an excitation wavelength of 350 nm [19]. We confirmed that EGCG had no obvious effects on ThT and ANS fluorescence under the experimental conditions of this study.…”
Section: Preparation and Characterization Of Lysozyme Fibrilssupporting
confidence: 78%
See 1 more Smart Citation
“…ThT fluorescence was measured in a mixture of 33 g/mL lysozyme and 10 M ThT with excitation at 440 nm and emission at 484 nm in a Perkin Elmer LS55 spectrofluorimeter. The emission spectra of ANS fluorescence in the presence of lysozyme fibrils were recorded between 400 and 600 nm using an excitation wavelength of 350 nm [19]. We confirmed that EGCG had no obvious effects on ThT and ANS fluorescence under the experimental conditions of this study.…”
Section: Preparation and Characterization Of Lysozyme Fibrilssupporting
confidence: 78%
“…Lysozyme fibrils were prepared according to our previous reports with minor modifications [9,19]. Briefly, hen egg white lysozyme was dissolved in HCl solution (10 mM, pH 2.0) with or without EGCG to a final concentration of 10 mg/mL (0.7 mM).…”
Section: Preparation and Characterization Of Lysozyme Fibrilsmentioning
confidence: 99%
“…For example, lysozyme protofibrils can disintegrate erythrocyte membranes through intermolecular disulfide cross-linking of the membrane proteins (Huang et al 2009) and induce apoptosis-like death of neurons, fibroblasts and neuroblastoma cells (Malisauskas et al 2005;Gharibyan et al 2007). Amyloid Aβ peptide can scramble erythrocyte membrane with subsequent cell death (Nicolay et al 2007).…”
Section: Other Mechanisms Of Fibrilmembrane Interactionsmentioning
confidence: 99%
“…Membrane damage produced by the early protein oligomers is regarded as the main cause of cytotoxicity (Kinnunen 2009;Relini et al 2009;Stefani 2010;Butterfield and Lashuel 2010). Cytotoxic action of protein oligomers can be attributed to compromised membrane integrity (Meratan et al 2011;Huang et al 2009), formation of non-specific ion channels (Caughey and Lansbury 2003), uptake of lipids into the fibers growing on a membrane template (Sparr et al 2004;Engel et al 2008), alterations in the intracellular redox status and free calcium level (Arispe et al 1993;Squier 2001;Tabner et al 2002), and impaired functions of membrane proteins (Stefani 2007). Several lines of evidence suggest that oligomeric species display higher membrane-binding affinity compared to mature fibrils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation